2016
DOI: 10.1002/jib.346
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of caesium and potassium from Japanese apricot (Prunus mume Sieb.et Zucc.) to Japanese apricot liqueur (Umeliqueur)

Abstract: The potential contamination with radionuclides released by the Fukushima Daiichi Nuclear Power Plant Accident following the great east Japan earthquake and tsunami in March 2011 of agricultural products and processed foods derived from them is a matter of on-going concern. The stable 133 Cs is a useful indicator for predicting the behaviour of radioactive Cs, and potassium (K) is a congener of Cs. In this study, the distribution of 133 Cs and K in Ume fruit, and the transfer of 133 Cs and K from Ume fruit to U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…On average, the 137 Cs content of wine compared with grapes was about 0.40 (0.40 Bq L −1 wine per Bq kg −1 grapes), and the 90 Sr content of wine compared with grapes was about 0.23 (0.23 Bq L −1 wine per Bq kg −1 grapes) (Hellmuth et al 1989). Okuda et al (2016) reported that about 80% of cesium in the fruit of Japanese apricot was retained in the liqueur made from the fruit; this corresponded to a cesium concentration in the liqueur of approximately 20-25% of that in the fruit (processing factor about 0.25 Bq L −1 liqueur per Bq kg −1 fruit).…”
Section: Manufacture Of Alcoholic Beveragesmentioning
confidence: 99%
“…On average, the 137 Cs content of wine compared with grapes was about 0.40 (0.40 Bq L −1 wine per Bq kg −1 grapes), and the 90 Sr content of wine compared with grapes was about 0.23 (0.23 Bq L −1 wine per Bq kg −1 grapes) (Hellmuth et al 1989). Okuda et al (2016) reported that about 80% of cesium in the fruit of Japanese apricot was retained in the liqueur made from the fruit; this corresponded to a cesium concentration in the liqueur of approximately 20-25% of that in the fruit (processing factor about 0.25 Bq L −1 liqueur per Bq kg −1 fruit).…”
Section: Manufacture Of Alcoholic Beveragesmentioning
confidence: 99%